Mapping the Scientific Literature on Mangrove Conservation in Indonesia: A Bibliometric Analysis to Environmental Research - Husna Jazimatul; Wijayanti Ima; Budiastusi Wiratmo Liliek; Indrahti Sri; Naryoso Agus; Edzan Che Nasir Nor; Patria Ratna Maharani; Mulyaning Andini Berliana; Raihan Putra Ratarno Dhaka (E3S Web of Conferences, 2023)
In 2022, the Global Mangrove Alliance (GMA) released the latest map of the world's mangroves. Southeast Asia is home to the most extensive mangrove forests, with Indonesia contributing one-fifth of the world's total mangrove area. Given this, government policies and in-depth studies are needed. The purpose of this study is to contribute to and complement the studies conducted by previous researchers. This study uses the bibliometric analysis methodology with VOSviewer and the biblioshiny package in RStudio. This study investigates the development of international publications and research on mangroves in Indonesia. The methodology and framework were adapted from the bibliometric analysis procedures developed by Donthu in 2021. The published results and findings on mangroves increased by 475%. There is a scientific collaboration between world scientists and Indonesian scientists, for example, the collaboration of Kauffman J.B. Alongi D.M., Murdiyarso D., and Basyuni. The book World Atlas of Mangroves, written by M. Spalding et al., and the book Mangrove Guidebook for Southeast Asia, written by Giesen et al., have received many citations and have become essential references for many world mangrove researchers. Many Scopus journals that have a high h-Index and ranking (Q) have published publications on mangrove ecosystems in Indonesia, for example, Biodiversity (Q2), AACL Bioflux (Q2), and Ocean and Coastal Management (Q1). Many keywords related to various aspects of the mangrove ecosystem were found: conservation, biodiversity, blue carbon, ecotourism, climate change, remote monitoring, avicennia marina, rhizophora, and seagrass.